Effects of electromagnetic fields and packaging shape on physicochemical and microbiological characteristics of water - Abdelrazik Abdelsamie , Maher Abdelaleem (2015)
The production of Halal food is an integrated process that produces not only food that is ritually blessed, but must be safe, innocuous and healthy (Tayyib). The widespread use of electromagnetic (EM) waves and its ability to induce non-thermal effects in water solutions calls for a study of the relationship between environmentally abundant electromagnetic fields (EMFs) and packaging shape, to determine its effects on the physicochemical and microbiological characteristics of water during storage. The study was accomplished through developing computer simulation models of four water containers and then performing EM simulation. The validation of the computer simulation was done by studying the exposure of the containers to 2.4GHz EM waves and environmentally abundant EMFs. Two high and low ionic content solutions representing natural mineral drinking water and H2O-NaCl was used as a samples, respectively. The EM simulation results showed that the absorption of EM energy was changed by changing the shape of the container. After exposure to free space 1.3V/m plane waves,the total specific absorption rate (SAR) values of EM energy absorbed by water at2400MHz for vertical polarization were 0.0292, 0.0203, 0.0201 and 0.01723 mW/kg,for pyramidal, rectangular, square and cylindrical container models, respectively. The maximum values of the electric field induced in water in the reverberation chamber after exposure to 1 W EM radiation were 111.7, 22.9, 33.6 and 60.3 V/m for pyramidal,rectangular, square and cylindrical container models respectively. Although there were variations in the physicochemical and microbiological parameters between water stored in shielded and unshielded container groups, as well as between water in the same group of containers, the water remained within the permissible guidelines of the WHO. There were significant variations in the values of zeta potential and cluster size of water of H2O-NaCl and natural mineral drinking water stored in the unshielded containers exposed to EM waves, as shown in the results of the 17O Nuclear Magnetic Resonance NMR and Raman spectroscopy techniques, respectively. It can be concluded that the variations in the electric and magnetic fields and SAR values induced in water affected the cluster size of water molecules, which were reflected in the results of particle size and the crystallization mode of water’s mineral content in both high and low ionic content solutions. This might indirectly affect the physicochemical and microbiological characteristics of the natural mineral drinking water. The results of the study are significantly useful in obtaining parameters for water solutions storage and packaging process optimization.